2019
DOI: 10.1128/jvi.00577-19
|View full text |Cite
|
Sign up to set email alerts
|

Nipah and Hendra Virus Glycoproteins Induce Comparable Homologous but Distinct Heterologous Fusion Phenotypes

Abstract: Nipah and Hendra viruses (NiV and HeV) exhibit high lethality in humans and are biosafety level 4 (BSL-4) paramyxoviruses in the growing genus Henipavirus. The attachment (G) and fusion (F) envelope glycoproteins are both required for viral entry into cells and for cell-cell fusion, which is pathognomonic of henipaviral infections. Here, we compared the fusogenic capacities between homologous and heterologous pairs of NiV and HeV glycoproteins. Importantly, to accurately measure their fusogenic capacities, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 62 publications
3
47
0
Order By: Relevance
“…The frequent sample level co-detection of TevPV with all other viruses (highest median interaction coefficients) suggests it may play a central role in driving co-infections, potentially through immunosuppression or perhaps through activation of latent infections, as has been observed in herpesvirus co-infections [58]. Alternatively, a recent study has demonstrated that interactions between glycoproteins in HeV-NiV co-infections may promote viral entry and, perhaps, increase viral loads [59]. Further empirical and modelling studies are warranted to assess whether this approach could contribute to improved spillover predictions.…”
Section: Discussionmentioning
confidence: 99%
“…The frequent sample level co-detection of TevPV with all other viruses (highest median interaction coefficients) suggests it may play a central role in driving co-infections, potentially through immunosuppression or perhaps through activation of latent infections, as has been observed in herpesvirus co-infections [58]. Alternatively, a recent study has demonstrated that interactions between glycoproteins in HeV-NiV co-infections may promote viral entry and, perhaps, increase viral loads [59]. Further empirical and modelling studies are warranted to assess whether this approach could contribute to improved spillover predictions.…”
Section: Discussionmentioning
confidence: 99%
“…We postulated that the enhanced cell membrane fusion observed for the CDV-H 5804/F SPA pair might be related to a lower binding avidity at the H/F interface. This was based on the observation that H/F dissociation is essential for the fusion process [ 23 , 24 ]. In order to test our hypothesis, we evaluated the relative strengths of association for different combinations of CDV-H and F proteins by coimmunoprecipitation (co-IP) assays.…”
Section: Resultsmentioning
confidence: 99%
“…The strength of envelope protein interaction is known to affect fusion activity [65,66]. Yet, we did not pursue assessment of the H and F physical interaction since our efforts to detect equally the F glycoprotein of the two viral species by means of a FLAG-tag specifically abrogated heterotypic complementation (Muñoz-Alía and Russell, unpublished data, 2019) [67].…”
Section: Discussionmentioning
confidence: 99%